Students’ Perception in Using ProProfs Online Quizzes as an Assessment Tool in English Classroom - Rizqi Febrian Pramudita; Meiga Rahmanita; Peni Arianita Wardani; Muhamad Farhan; Suyik Binarkaheni (P3M Politeknik Negeri Jember, 2023)
There have been several ICT platforms used in assessment, one of which is ProProfs. The use of Proprofs, however, has not been widely known compared to other platforms, such as Quizziz and Kahoot!. This research attempted to find out the students’ perception towards the use of ProProfs in doing exercise in their Intermediate English Class. This was qualitative research, which used questionnaires and interviews to collect the data. The subjects were 127 students of Politeknik Negeri Jember, majoring in Management of Agroindustry. The result showed that most students think that having quizzes using ProProfs were interesting and challenging, and thus, made ProProfs become one of the assessment tools in class that is worth implementing. However, further research still needs to be done to explore the use of ProProfs in all levels of education.